(untitled) (Bangladesh Journal of Nuclear Medicine, 2019)
Objective: Worldwide, osteoporosis in postmenopausal women is a common public health problem. The measurement of bone mineral density (BMD) of spine and hip using central dual energy X-ray absorptiometry (DXA) is the most standard technique to diagnose osteoporosis. But in many circumstances, measurement of spine or hip BMD is quite difficult to carry out where wrist BMD can be used as an alternative. Moreover, wrist BMD can be done with smaller, cheaper, portable peripheral devices for screening osteoporosis at primary health care level. The objective of the study was to explore the agreement of wrist BMD with spine and hip BMD in postmenopausal women. Patients and Methods: This observational, cross sectional study was carried out at National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Bangabandhu Sheikh Mujib Medical University (BSMMU) campus, from July 2017 to June 2018. A total of 110 postmenopausal women referred to NINMAS for BMD measurement were enrolled in this study after fulfilling selection criteria. BMD of spine, right and left hip and wrist of enrolled subjects were measured by dual energy X-ray absorptiometry (DXA) scan by Stratos DR Bone densitometer. Results: Agreement analysis done by kappa statistics revealed kappa value of 0.930 (p<0.05), 0.782 (p<0.05) and 0.635 (p<0.05) between wrist and spine BMD, wrist and right hip BMD and wrist and left hip BMD, respectively. In Bland-Altman analysis, the mean difference of T-score measured by wrist and spine was -0.007 ± 1.361, wrist and right hip was -0.645 ± 1.271 and wrist and left hip was -0.450 ± 1.259 with 95% of differences were found in between -2.674 and 2.660, -3.136 and 1.846 and -2.917 and 2.017, respectively. Positive significant Pearson’s correlation was observed between wrist BMD and spine BMD (r=0.664; p=0.001), wrist BMD and right hip BMD (r=0.719; p=0.001) and wrist BMD and left hip BMD (r=0.727; p=0.001). Conclusion: This study results showed an excellent kappa agreement between wrist and spine BMD with good kappa agreement of wrist with right and left hip BMD as well as in Bland-Altman analysis, the mean differences of T-score between wrist andspine, wrist and right hip and wrist and left hip were small. The biases between the methods were considered not significant suggesting that these sites can be used interchangeably for measurement of BMD. Hence, wrist BMD can be used with regular skeletal sites (spine and hip) as an effective method of diagnosing osteopenia and osteoporosis by DXA where spine or hip BMD is difficult to carry out as well as it can be used for osteoporosis screening at primary health care level by portable peripheral DXA device to initiate early treatment to reduce fracture risks. Bangladesh J. Nuclear Med. 22(1): 41-46, Jan 2019